KAPASITAS AEROBIK MAKSIMAL ATLET PENCAK SILAT PERGURUAN PAGAR NUSA - Saprian, Saprian; Purnomo, Edi; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Aerobic capacity is a problem that is often faced by sports athletes, especially pencak silat, many athletes often experience rapid fatigue in competing. This results in decreased concentration of athletes in competing and it is difficult to receive input from coaches for athletes who experience fatigue. So this is the background of the author to examine this problem. This study aims to measure the maximum aerobic capacity of pencak silat fence athletes. The method used in this research is a descriptive survey. The population in this study were pencak silat athletes from fence Nusa, and the research sample consisted of 20 people with different fighting classes. The instrument used in this research is the Bleep Test research technique (run back and forth). By using a voice recording that reads "TuT" with a distance of 20 meters and an assessment tool for the results of the Bleep Test. with a number of 2 people with a percentage of 10% very good results with a number of 2 people with a good percentage of 10% excellent results with a total of 0 and a percentage of 0%. So there are surprising results in the research that has been conducted on 20 tested respondents, there are 12 respondents who have very poor aerobic capacity results and greatly affect the physical endurance of an athlete.